2016
DOI: 10.1097/prs.0000000000002107
|View full text |Cite
|
Sign up to set email alerts
|

Primary versus Flap Closure of Perineal Defects following Oncologic Resection: A Systematic Review and Meta-Analysis

Abstract: Therapeutic, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
134
2
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(173 citation statements)
references
References 41 publications
7
134
2
7
Order By: Relevance
“…In our series, there was an overall 30‐day healed perineal wound rate of 72% and low complication rates of the reconstructed site (28%) and the donor site (20%). These rates are lower than a recent systematic review that demonstrated perineal and donor site complication rates of 52.9% for gracilis flaps . This may highlight the importance of a familiar combined multidisciplinary approach, as there is a technical learning curve owing to the complexity of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, there was an overall 30‐day healed perineal wound rate of 72% and low complication rates of the reconstructed site (28%) and the donor site (20%). These rates are lower than a recent systematic review that demonstrated perineal and donor site complication rates of 52.9% for gracilis flaps . This may highlight the importance of a familiar combined multidisciplinary approach, as there is a technical learning curve owing to the complexity of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…The pelvic dead space can result in abscess formation, intestinal occlusion, or fistulization due to strong adhesions that form on the pelvic walls. These complications can be prevented by using techniques such as a muscle flap, silicone prosthesis, or the omentum to fill this space …”
Section: Resultsmentioning
confidence: 99%
“…When the procedure's morbidity remains low, it is recommended to use the best performing pedicled myoperitoneal or myocutaneous flaps …”
Section: Resultsmentioning
confidence: 99%
“…объединен опыт 10 исследований с общим числом 566 пациентов по использованию кожно-мышечных лоскутов (доста-точно репрезентативными исследованиями были со-чтены только работы по использованию VRAM-лоскута и m. gracilis). Авторы отметили достоверное снижение частоты тяжелых осложнений со стороны промежностной раны при использовании пластики: отношение рисков 3,64; 95 % доверительный интервал 1,43-7,79; p = 0,005 [44].…”
Section: заключениеunclassified